Eric Rohmer : Interviews - Rohmer, Éric, 1920-2010 (Book collections on Project MUSE., 2013)
The 1969 film Ma Nuit chez Maud catapulted its shy academic film director Eric Rohmer (1920-2010) into the limelight, selling over a million tickets in France and earning a nomination for an Academy Award. Ma Nuit chez Maud remains his most famous film, the highlight of an impressive range of films examining the sexual, romantic, and artistic mores of contemporary France, the temptations of desire, the small joys of everyday life, and sometimes, the vicissitudes of history and politics.